(Z)-Ethyl 2-hydroxyimino-2-(4-nitrobenzyl)ethanoate - Caracelli, I.; Trindade, A.C.; Moran, P.J.S.; Hinoue, L.; Zukerman-Schpector, J.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C(11)H(10)N(2)O(6), has a Z conformation about the C = N bond of the oxime unit. There are significant twists from planarity throughout the molecule, the most significant being between the hydroxyimino and ester groups which are effectively orthogonal with an N-C-C-O(carbonyl) torsion angle of 91.4 (2)degrees. The crystal packing features oxime-benzoyl O-H center dot center dot center dot O contacts that lead to chains along [010] and C-H center dot center dot center dot O interactions also occur.